Análisis crediticio a las cuentas por cobrar (cartera) de la Cooperativa de Ahorro y Crédito Pujilí ldta., ubicada en el cantón Pujilí, provincia de Cotopaxi al periodo 1 de enero al 30 de diciembre del 2011 - Analuisa Guangasi, Gloria Cecilia (2015)
The credit analysis is a stage of evaluation about information, so it can be determinedif applicants are at the level of the company. The principal objective of this research was to establish a series of methodological, conceptual and content tools and in this way the credit analysis can be quite effective in the Cooperative of savings and credit Pujilí, (COACP) located in the same canton.This clarifies major and important concepts such as risk and its derivatives, the types of credit that can be offered by the financial institutions. It is expanded the theory of the five "Cs" of credit and its importance into the assessment of credit risk. It contains basic information about the analyzed institution that in this case is “COACP”. It is analyzed policies and institutional settings as well as the organizational structure. It is to say that, it shows the prior knowledge of the organization. So, in this way, it can be obtained results through survey and through the observation of the staff and fellows at COACP. I t is shown the analysis of holding credit. There is an overview of the institution analysis. It is to say what is concerned to commercial loans, consumer and housing during the period January to December 2011. It was used graphs and charts with dollar prices. Thinking about this, It is presented the credit scoring which will serve the credit counselor because it is a tool where it is going to be recorded all the fellow´s information, so that it can emit if it is possible or not to give the credit to the fellows.